Expansion of the northern distribution of Neoraimondia arequipensis subsp. gigantea (Werd. & Backeberg) Ostolaza - Alfaro Aguilera, Rubén (2020)
Neoraimondia arequipensis subsp. gigantea is registered in the dry forests of Tumbes, expanding its geographical distribution in northern Peru, based on the phenotypic identification of 70 individuals and genotypic by sequencing the matK gene (Maturase K gene). The habitat of this species is characterized by the presence of stony and rocky soil, located adjacent to areas of ravines and altitudes between 20 to 60 meters above sea level. In addition, we include the record of biological interactions of this cactus with endemic fauna and flora of the department of Tumbes.